2018
DOI: 10.17531/ein.2018.4.12
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic diagnostic strategy based on reliability analysis and distance-based VIKOR with heterogeneous information

Abstract: This paper presents a dynamic diagnostic strategy based on reliability analysis and distance-based VIKOR with heterogeneous information. Specifically, the proposed method uses a dynamic fault tree (DFT) to describe the dynamic fault characteristics and evaluates the failure rate of components using interval numbers to deal with the epistemic uncertainty. Furthermore, DFT is mapped into a dynamic evidential network (DEN) to calculate some reliability parameters and these parameters together with test cost const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
(25 reference statements)
1
5
0
Order By: Relevance
“…From the ranking results given in Table 2, it can be observed that all methods show X2 is the worst choice. In addition, the ranking results obtained by our proposed method are completely consistent with [46], [28], which shows that the method proposed in this paper is effective. The inconsistent results between different methods can be understood by the different expressions of information and different weighting methods.…”
Section: F An Illustrative Examplesupporting
confidence: 77%
See 4 more Smart Citations
“…From the ranking results given in Table 2, it can be observed that all methods show X2 is the worst choice. In addition, the ranking results obtained by our proposed method are completely consistent with [46], [28], which shows that the method proposed in this paper is effective. The inconsistent results between different methods can be understood by the different expressions of information and different weighting methods.…”
Section: F An Illustrative Examplesupporting
confidence: 77%
“…To illustrate the effectiveness of the proposed multi-source heterogeneous fault diagnosis method, some existing methods are compared with our proposed method in this paper, which include Ref. [28], [46], [47]. We take the example shown in [46] so that we can compare the proposed method with existing methods.…”
Section: F An Illustrative Examplementioning
confidence: 99%
See 3 more Smart Citations